Integrative treatment program for the treatment of children with autism spectrum disorder: A prospective observational case series - Lee, Boram; Park, Serin; Kwon, Hyun Jeong; Hwang, Gwi Seo; Kim, Moonju (Frontiers in Neurology, 2023)
Background: In a situation where conventional treatments for autism spectrum disorder (ASD) are labor-intensive and there are concerns about the side effects of conventional medications, a 6-month integrative treatment program, including herbal medicine (HM), Floortime, and sensory enrichment therapy (SET) has been used on children with ASD in Korean medicine clinical settings. Methods: We observed the treatment responses of 18 children with ASD (66.7% male, mean age 3.9 ± 0.9 years) to the integrative treatment program as part of a prospective, single-center, observational case series. Individualized HMs were administered according to the patient's symptoms, and parents were instructed to perform Floortime and SET with their children at home for 2 h and 20 min a day, 5 days a week, respectively. The Childhood Autism Rating Scale (CARS) and Autism Behavior Checklist (ABC) were used to evaluate the core symptoms of ASD. A linear mixed model for repeated measures was used for analyzing the effect of the program over time, and logistic regression used to explore the predictors of treatment response. Results: The CARS and ABC scores were significantly improved from 34.58 ± 6.27 and 69.28 ± 15.73 at baseline to 28.56 ± 6.05 and 39.67 ± 20.36 after 6 months (p<0.0001, respectively). No serious adverse events were reported, and compliance with HM, Floortime, and SET was high at >90%. Conclusion: This 6-month integrative treatment program appears to be a potentially effective, safe, and feasible option for children with ASD. Low baseline CARS scores may be predictors of higher treatment response.